Does Global Budget promote the construction of integrated healthcare delivery system? Evidence from Sanming, China - Liangwen Zhang; Xingyuan Yu; Ya Fang (BMC Public Health)
Abstract Background The Chinese government is advancing the development of the County Medical Community (CMC) to establish an integrated healthcare delivery network and ensure health equity. Recently, Global Budget (GB) economic incentives have been implemented in CMC. Although the impact of GB on medical expenditure has been demonstrated, there is little evidence on whether GB promotes collaboration among various providers. Methods This article takes Sanming City, a typical example of China's healthcare reform, as a case study, and uses data from 2016 to 2023 on the operation of CMC. Interrupted time series analysis was used to evaluate the long-term impact of GB on inpatient costs, cost structure and service delivery. Results The analyses indicate that, although the direct impact of the GB on inpatient costs is not significant, it sustains a rational structure of inpatient cost and optimizes the delivery of inpatient services at all levels of institutions. With respect to inpatient cost structure, the proportion of drug costs in secondary hospitals (SHs) (β 3  = 0.127, P < 0.001) and tertiary hospitals (THs) (β 3  = 0.120, P < 0.05) increased after the GB, the proportion of testing and inspection costs in primary healthcare institutions (PHIs) decreased (β 3  = -0.215, P < 0.05). In terms of service delivery, the average length of stay in SHs (β 3  = -0.053, P < 0.05) and THs (β 3  = -0.032, P < 0.001) decreased, and the admission per 100 outpatients (β 3  = 0.058, P < 0.001) in PHIs increased. The robustness analysis corroborated the robustness of the results. Conclusions This article provides empirical evidence that GB mechanisms can enhance service coordination among different levels of healthcare providers, which provides valuable lessons for promoting integrated healthcare and achieving health equity in China and in low- and middle-income countries.